Intercropping Ethiopian Trifolium species with wheat - Kahurananga, J. (Cambridge University Press, 1991)
Trials were conducted to test methods of intercropping annual Ethiopian clovers, Trifolium spp, with wheat. Several different clover varieties, sowing methods, plant spacings, planting dates and rates of phosphorus application were compared. The results indicated that the intercropping of Ethiopian clovers in wheat has potential under African highland conditions.